Inequality is bad for growth of the poor (but not for that of the rich) - van der Weide, Roy; Milanovic, Branko (Washington, DC, 2014)
"This paper presents evidence on the determinants of cross-border mergers and acquisitions in services sectors. It develops a stylized model of mergers and acquisitions that predicts that the incidence of merger and acquisition deals depends, inter alia, on the target economy's size, industrial structure and investment policies, as well as on bilateral transactions costs. These predictions are examined with bilateral merger and acquisition flow data and detailed information on policy barriers from a new database of restrictions on services investment. The analysis finds that: (1) geographical factors affect mergers and acquisitions in services and manufacturing similarly but cultural factors affect mergers and acquisitions in services more than in manufacturing. (2) Controlling for these bilateral factors, restrictive investment policies reduce the probability of merger and acquisition inflows but this negative effect is mitigated in countries with relatively large shares of manufacturing and (to a lesser extent) services in gross domestic product. The same results hold for the number of merger and acquisition deals received. These findings suggest that the impact of policy is state-dependent and related to the composition of gross domestic product in the target economy."